Emissão de inflorescência, biologia reprodutiva e armazenamento de grãos de pólen em Butia capitata (Mart) Becc sob condições de cultivo - Wlly Polliana Antunes Dias (2018)
The Coquinho Azedo (Butia capitata (Mart.) Becc.) is a palm native of the Cerrado with great economic and ecological importance. Currently, the extractivism, associated with deforestation, has contributed to include the Coquinho Azedo in the category of vulnerable to extinction. The objective of this study was to characterize inflorescence emission, to describe aspects of reproductive biology and to evaluate the storage potential of Butia capitata (Mart.) Becc pollen grains. In the first experiment, an arrow leaf was marked per individual, one in May and the other in November 2016 and followed up until the harvest of the bunch in his armpit. In the second, for the characterization of floral biology, fifteen inflorescences were followed and in that period changes in its morphology were observed. To evaluate the stigmatic receptivity, during ten days, the flowers of eight individuals were immersed in 6% hydrogen peroxide (H2O2) solution for 5 minutes. In addition, fifteen inflorescences were monitored daily for the presence of staminate and pistillate flowers in anthesis, in addition to the absence of flowers in anthesis. In the third experiment, the storage capacity of the pollen grains was evaluated. These were stored for six months in three conditions: ambient (± 25°C), refrigerator (4°C ± 2) and freezer (-20°C ± 2). The vitality of these grains was evaluated by in vitro germination. In the fourth experiment the following tests were performed with the reproductive system: xenogamy, manual self-pollination, spontaneous self-pollination, apomixia and open pollination. The leaves marked in November 2016 showed a vegetative growth faster, reducing the time necessary for the appearance of spaths in his armpit. In addition, the number of spathes produced by these leaves was larger than the leaves marked in May. Consequently, the production of fruit bunches and the weight was also higher. The absence of anthesis of flowers of both sexes in the inflorescence demonstrates that the flow of pollen inside the inflorescence is rare, predominating in the species cross pollination. The pollen grains stored in the refrigerator and in the freezer showed pollen tube growth up to 180 days, differing significantly from grains stored at room temperature, which presented a small germination rate only in the first month. The cross pollination and open pollination were superior to the other treatments. For spontaneous self-pollination and apomixia no fruit fixation was observed, while artificial self-pollination, despite a small rate, resulted in fructification.